Fenomena Cyber Religion sebagai Ekspresi Keberagamaan di Internet pada Komunitas Shift (Cyber Religion Phenomenon as a Religious Expression on the Internet in the Shift Community) - Hariya Toni; Dede Mercy Rolando; Yasril Yazid; Robby Aditya Putra (Jurnal Dakwah Risalah, 2021)
This article aims to determine the form of Shift's religious expression and the factor of the Shift community's interest in the context of cyberreligion. The research method is qualitative with the type of phenomenological research. There are 5 research subjects (subscribers) and the research object of the YouTube channel Shift. The interactive model analysis technique of Miles & Huberman from the results of data collection that the authors get. The results showed that the phenomenon of cyberreligion has touched various circles and was used by Ust. Hanan Attaki by establishing a Shift which targets the younger generation in the form of online religion. The use of YouTube as a means of spreading Shift's da'wah is categorized into the File-Sharing category. The study, which is nicely packaged by Ust. Hanan Attaki, has made it loved by the younger generation as an alternative in their religious information.